PENILAIAN PELAKSANAAN PENDIDIKAN KESEHATAN BERDASARKAN PEDOMAN PELAKSANAAN UKS DAN OTTAWA CHARTER - Intan Putri Rahayu; Fika Ardiana; Inriza Yuliandari; Wahyu Febriawan; Jayanti Dian Eka Sari (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Health is the most important thing that must be known by many people. Awareness of the importance of health needs to be instilled early on so that children can easily apply it in their lives. To support this, the government launched a health promotion program in schools. Health promotion is the way in which efforts can be made to improve public health and the environment in the community. Many ways can be done so that people can do disease prevention, one of them is by applying health education. Health education is an effort to provide guidance to learners about health covering physical, mental and social aspect in order to improve and develop with good knowledge, attitude, and practice related to healthy life principle. Base on of this background, the authors do research to determine the state of health education in schools. The purpose of this research is to know the implementation of health education in the educational institution in accordance with the guidelines of the implementation of UKS and Ottawa Charter. The method of implementation of this activity is to use interview techniques and practices based on an instrument that has been validated by researchers along with supervisors. This activity was conducted on May 2nd, 2018 for 10 respondents, one coach, four students, and five members of the Red Cross Teen. The institution that researchers chose was SMP Negeri 1 Giri Banyuwangi. The conclusion of this study indicates that the implementation of health promotion in SMP Negeri 1 Giri Banyuwangi still not in accordance with the Guidelines for Implementation of UKS in School Year 2014, so the result of this research can be used as advocacy material to SMP Negeri 1 Giri Banyuwangi. Keywords: Health Promotion, Health Education, UKS, and Ottawa Charter